Love those eyes : alluring eye-makeup looks for every occasion - Ellis, Sarah Jane; Mazzone, Elisa (London: Ilex, 2017)
In Love Those Eyes, Sarah Ellis and Elisa Mazzone bring you 50 gorgeous eye-makeup recipes. These mouth-watering ideas will delight all the more when you apply them to your own eyes. As with any great recipe collection you are inspired to adjust and re-balance the elements to suit your own eye shape, complexion or mood. Featuring light looks to warm your day, cool powerful looks to say you mean business, carefree looks for out and about, dramatic looks for turning those heads. And when you need to party? Look no further - you will rock it! Complete all looks with your favourite mascara or lashes for the perfect finish. They say beauty is in the eye of the beholder. It will be.
In English.
Keywords: Artet boterore; Arti vizual-kozmetika; Arti modern-grimi; Cosmetics; Beauty, Personal. -- Kujdesi personal-e bukura; Eye -- Care and hygiene-kujdesi dhe higjena; Artiste boterore; Grimi-Grimieret-teknika-make up-teknika-perdorimi-syte; Catwalk-pasarelat-kozmetika-mjetet-moda-fashion